Gambaran Faktor Psikologis yang Mempengaruhi Proses Terapi Anak dengan Autism Spectrum Disorder - Rizky, Elvina; Noor, Irfan; Fadhila, Mahdia (Jurnal Al-Husna, 2020)
Autism spectrum disorder is a developmental delay in children which is characterized by disorders in social aspects, communication, behavior, and language. Treatment that will be given to children with autism is therapy, like speech therapy, behavior, occupation, and sensory integration. Based on preliminary studies and earlier research, I found things that can affect both those that support and inhibit the implementation of therapy. Therefore This study aims to decide what psychological factors affect the process therapy at the Center for Disability and Inclusion Education in South Kalimantan Province. This study uses a type of field research with a qualitative descriptive approach. The subjects in this study amounted to 6 therapists who have worked for 5 years at PLDPI. The results showed that therapeutic services at PLDPI, there are factors that influence the process and success of therapy. Internal factors that support the therapeutic process in PLDPI is the wishes of the child, age of the child, level of autism disorders, IQ child, child's mood, affection therapist, therapist's patience and therapist's sincerity, ritual therapist (praying, prayer dhuha, reading istighfar and basmalah), the intention of the therapist, understanding of children, enthusiasm and attendance consistency therapist, professional attitude. While external factors that support is self-awareness of people old in adopting a diet, parental support, the role of parents at home, therapist support, number adequate therapist, therapist collaboration with parents, adequate facilities and infrastructure and a therapeutic schedule that meets the target and therapy program that suits the child's needs. The internal factors that inhibit the child's condition such as hyperactivity, hypoactive, tantrum, sick, minimal eye contact, speech difficulties and disobedience and therapists who cannot be controlling emotions. While the external factor is the parents' wants.